Effect of laser peening without coating on mechanical and microstructural behaviour of SS 304 stainless steel. (December 2022) - Nataraj, M.V.; Swaroop, S.
Abstract: This present work investigates the influence of laser shock peening without coating (LPwC) of SS 304 stainless steel. To understand the effect of deformation behaviour, laser power densities of 3, 6 and 9 GW cm −2 were employed. The Residual stress and microhardness (HV) were investigated at surface and depth direction. The maximal value of compressive residual stress (−340 MPa) reached a depth of 50 µm for the laser intensity of 9 GW cm −2 . Micro hardness significantly increased to 71.11% for 9 GW.cm −2 compared to the unpeened sample. To observe the mechanical twinning and grain refinement the Electron backscattered diffraction (EBSD) was carried out. A Transmission electron microscope (TEM) was also performed to know the nano twins and dislocation movement in the laser peened samples. Results showed that laser peening without coating process would cause a significant improvement on surface properties such as compressive residual stress, surface roughness, microhardness, and microstructure and grain refinement. Graphical Abstract: ga1